KEPUASAN PENYEWA TERHADAP FAKTOR-FAKTOR PEMILIHAN KANTOR SEWA KELAS A FUNGSI MAJEMUK DI SURABAYA - Antusias Nurzukhrufa; Purwanita Setijanti; Asri Dinapradipta (Prodi Arsitektur UNIVERSITAS KEBANGSAAN, 2019)
Abstract: The growth of the supply and demand index of rental offices in Surabaya is the highest in Indonesia. However, the occupancy rate has decreased except in class A rental offices. Decrease in occupancy rate is influenced by dissatisfaction of tenants to the high rental price factor and causes the tenant not to extend the rent. The quality services of class A rental offices multifunction in Surabaya can be considered successful because the tenants have persisted in extending the leases. Therefore, it is necessary to know about the level of satisfaction of tenants to the factors that influence the choosing of class A rental offices multifunction in Surabaya. This research is included in the positivism paradigm with quantitative methods. The analysis technique uses quantitative descriptive statistics by calculating the mean and standard deviations mapped to the Cartesian diagram. This research results two findings. First, the three most satisfied factors i.e.